Análise do programa luz para todos como vetor de desenvolvimento no estado do Ceará - 2004 a 2008 - Silva, Jurandy Xavier da (2016)
The subject of this dissertation is to shed light on the Federal program named Programa Nacional de Universalização do Acesso e Uso da Energia Elétrica - Programa Luz para Todos, which was set up by specific law whose main aim is nothing more than providing free connection to the resident poor rural areas counting approximately 2,5 million residences all over the country. Further, the Luz para Todos program intends to maintain the peasant in his local area and as consequence to reduce the countryside-city migratory moves. In particular, the Luz para Todos aimed to electry 112,000 rural households by the end of 2008 in the case of Ceara state. In order to achieve this stated purpose as well as to consider supplementary applications, namely to oversee that the program will indeed be implemented along social lines (reducing both poverty and marginalization), the State Management Committee including various associations from the civil society was created. It should be noted that the empirical research is totally based on the incontrovertible premises put forward by the Program by means of them one could identify the pros and contra concerning the Program here in Ceará.